The effects of finish type on permeability and organoleptic properties of python (Python reticulatus) skin finished leather - Emiliana Kasmudjiastuti; Rihastiwi Setiya Murti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2017)
In the leather industry, there are many different types of finish, i.e. two-tone, transparent, semi aniline and opaque/solid color. The composition formulation of each finish type is different so each will impact not only on the performance but also on the properties of the finished leather. The objective of this research was to investigate the effects of finish type (natural, aniline, semi-aniline, and two-tone) on permeability and organoleptic properties of python skin finished leather. This research focused on the finishing process with various finish types. The results showed that the effect of semi-aniline (I,II) finish type on water vapor permeability reduction is the highest when compared with natural (I, II); aniline (I,II) and two-tone finish types. Otherwise, the effect of semi-aniline (I,II) finish type on organoleptic properties is the lowest compared with natural (I, II); aniline (I,II) and two-tone finish types. The aniline I finish type has better organoleptic properties.Keywords: finish type, natural, aniline, semi-aniline, two-tone, python skin.